Insights into the gut microbiota of Nigerian elderly with type 2 diabetes and non-diabetic elderly persons. (2020)
Type 2 diabetes (T2D) is a prevalent non-communicable disease among the world's growing elderly population. The contribution of the gut microbiota to T2D in several Westernized countries has been established. However, there is little information on the role of the gut microbiota in T2D from the African continent where lifestyle and life expectancy are different. Aims: This study sought to investigate gut microbiota variation in relation to elderly people living with T2D. in Nigeria. Methods: Whole microbial community DNA were derived from the stool samples of healthy urban-dwelling elderly individuals and urban-dwelling elderly individuals with T2D. The V4 region of the 16S rRNA gene was Illumina- sequenced and analyzed using QIIME2. Results: Beta taxonomic diversity was significantly different between healthy elderly individuals and elderly in- dividuals with T2D. However, no difference in the alpha taxonomic diversity and predicted functional alpha diversity of the gut microbiota was observed. The genus Ruminococcus (T2D versus Healthy: 2.89% vs 2.21%), families Coriobacteriaceae (Collinsella, T2D versus Healthy: 2.62 % vs 1.25%) and Bifidobacteriaceae were enriched in elderly individuals with T2D, while members of Clostridiaceae (Clostridium, Healthy versus T2D: 5.6% vs 3.2%) and Peptostreptococcaceae (Healthy versus T2D: 3.45% vs 1.99%) were enriched in healthy volunteers. Pathways involved in amino acid biosynthesis were enriched in elderly individuals with T2D, while pathways involved in respiration and the biosynthesis of vital building blocks were enriched in healthy volunteers. Conclusions: The study demonstrated for the first time in an African elderly population that the abundance of Bifidobacteriaceae, Collinsella, and Ruminococcus within the gut varies in relation to T2D. Findings from this study suggest that the restoration of features associated with healthiness via the way of gut microbiota modification could be one step needed to improve elderly patient care.